In-class multitasking and academic performance - Junco, Reynol (Computers in Human Behavior, 2012)
Abstract: The omnipresence of student-owned information and communication technologies (ICTs) in today’s college classrooms presents educational opportunities but can also create learning problems. Specifically, multitasking with these technologies can interfere with the learning process. Indeed, research in cognitive science shows that there are clear performance decrements when trying to attend to two tasks at the same time. This study examines the frequency with which students multitask during class using a large sample (N =1,839) and examines the relationship between multitasking and academic performance as measured by actual overall semester grade point average (GPA). Students reported frequently text messaging during class but reported multitasking with other ICTs to a lesser extent. Furthermore, only social technologies (Facebook and text messaging) were negatively related to GPA.